2008
DOI: 10.1007/s00464-008-9861-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical fundoplication for extra-oesophageal symptoms of reflux

Abstract: Surgery can be an effective treatment in the majority of patients with extra-oesophageal symptoms of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
3
18
1
1
Order By: Relevance
“…These results are consistent with prior studies, which demonstrated postoperative resolution or improvement of typical symptoms [8,15,[18][19][20]. Study results showed excellent symptom resolution following both primary and reoperative paraesophageal herniorrhaphy, as evidenced by significant reductions in all composite and individual esophageal and extraesophageal symptom scores in the follow-up period when compared with preoperative scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with prior studies, which demonstrated postoperative resolution or improvement of typical symptoms [8,15,[18][19][20]. Study results showed excellent symptom resolution following both primary and reoperative paraesophageal herniorrhaphy, as evidenced by significant reductions in all composite and individual esophageal and extraesophageal symptom scores in the follow-up period when compared with preoperative scores.…”
Section: Discussionsupporting
confidence: 92%
“…Reoperative paraesophageal herniorrhaphy patients in this study showed near-complete resolution of their esophageal and extraesophageal symptoms, similar to other studies [14,17,19]. These findings somewhat contradict the findings of Khaitan et al in terms of satisfaction rates following primary or reoperative procedures.…”
Section: Discussioncontrasting
confidence: 57%
“…The symptomatic outcome of patients in this study supports the more promising results of other studies on patients with extraesophageal symptoms as the main indication for LNF [16,18,27,28,29]. The symptomatic outcome of LNF for LPR in our study is similar to LNF results for typical GERD symptoms, also at long-term follow-up [9,17].…”
Section: Discussionsupporting
confidence: 81%
“…The GIQLI questionnaire has been recommended by the European Association for Endoscopic Surgery for the assessment of quality of life after fundoplication [26]. The DeMeester reflux questionnaire is validated to assess reflux symptoms and the RSI has been validated in nontransplant patients as a marker of extra-oesophageal reflux [13], and has been used to assess the effects of fundoplication on extraoesophageal reflux [27,28].…”
Section: Discussionmentioning
confidence: 99%